2023
DOI: 10.1097/apo.0000000000000637
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Goniotomy With or Without Secondary Intraocular Lens Implantation in Pediatric Glaucoma Following Cataract Surgery: A Prospective Pilot Study

Yu Zhang,
Wan Chen,
Timothy P.H. Lin
et al.

Abstract: Purpose: To report the outcomes of a 120-degree goniotomy (GT) with or without secondary intraocular lens (IOL) implantation in glaucoma following cataract surgery (GFCS). Design: Prospective, observational study. Methods: Pediatric patients with GFCS who underwent standalone 120-degree GT or 120-degree GT combined with secondary IOL implantation (GT+IOL) from March 2022 to August 2022 at the Zhongshan Ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…IOP reduction is a surrogate outcome to quantify intervention effectiveness, 45 , 46 and randomized trials have consistently shown that a 20% reduction in IOP from baseline halved the 5-year rate of glaucoma onset in the Ocular Hypertension Treatment Study, 47 and a 25% reduction significantly delayed glaucoma progression in the Early Manifest Glaucoma Trial. 48 However, in the present study, the suppression of Car2 mediated by the dual-target CRISPR system led to an average 18% reduction in normal mice and 40% reduction in glaucoma model mice, which is comparable to the decrease in IOP previously reported with disruption of aquaporin 1 24 or mutant myocilin .…”
Section: Discussionmentioning
confidence: 99%
“…IOP reduction is a surrogate outcome to quantify intervention effectiveness, 45 , 46 and randomized trials have consistently shown that a 20% reduction in IOP from baseline halved the 5-year rate of glaucoma onset in the Ocular Hypertension Treatment Study, 47 and a 25% reduction significantly delayed glaucoma progression in the Early Manifest Glaucoma Trial. 48 However, in the present study, the suppression of Car2 mediated by the dual-target CRISPR system led to an average 18% reduction in normal mice and 40% reduction in glaucoma model mice, which is comparable to the decrease in IOP previously reported with disruption of aquaporin 1 24 or mutant myocilin .…”
Section: Discussionmentioning
confidence: 99%